Flexural behaviour of concrete beams reinforced with glass fibre reinforced polymer bars - Mohd.Sam, Abdul Rahman; Swamy, R. Narayan (Faculty of Civil Engineering, UTM, 2005)
Corrosion of steel reinforcement is one of the main problems facing the construction industries throughout the world. Many methods have been used to minimize the problem but without success. Thus, more durable reinforcements are highly needed to replace conventional steel. Glass Fibre Reinforced Polymer (GFRP) bars provide a good alternative reinforcement due to its non-corrodible characteristic. This paper presents the flexural behaviour of concrete beams, each measuring 150 x 255 x 2400 mm and reinforced with GFRP and stainless steel bars. The performance of the beams was analysed in terms of their load carrying capacity, load-deflection, load-concrete strain, load-reinforcement strain, cracking and mode of failure. The experimental results show that beams reinforced with GFRP bars experienced lower ultimate load, lower stiffness, and larger deflection at the same load level compared with control beam. However, the performance of the GFRP reinforced concrete beams improved slightly when stainless steel mesh was used as shear reinforcement.